Constructing coherence in the British short story cycle - Gill, Patrick; Kläger, Florian (Routledge, Taylor & Francis Group, 2018)
"The first major collection of essays on the contemporary British short story cycle, this volume offers in-depth explorations of the genre by comparing its strategies for creating coherence with those of the novel and the short story collection, inquiring after the ties that bind individual short stories into a cycle. A section on theory approaches the form from the point of view of genre theory, cognitive literary studies, and book studies. It is followed by investigations of hitherto neglected aspects of the generic tradition of the British short story cycle and how they relate to the contemporary outlook of the form. Readings of individual contemporary cycles, illustrating the form's multifaceted uses from the presentation of sexual identities to politics and trauma, make up the third and most substantial part of the volume, placing its focus squarely on the past decades. Unique in its combination of a focus on the literary traditions, politics and markets of the UK with a thorough examination of the genre's manifold formal and thematic potentials, the volume explores what is at the heart of the short story cycle as a literary form: the constant negotiation between unity and separateness, collective and individual, of coherence and autonomy"--
Keywords: anglicky psaná povídka -- dějiny; literární kritika; short stories in English -- history; literary criticism; eseje; essays